Objemné tumory s nejistou biologickou aktivitou lokalizované v pohrudnicní dutinĕ - Neoral, C; Dusková, M; Grygárková, L; Jezdinská, V; Kucerová, L; Klein, J; Bohanes, T (Rozhledy v chirurgii, 2000)
The authors discuss specific problems of an exact diagnosis and indication for surgical treatment in patients with large tumours in the pleural space. Our series includes even some rare tumours of varied histogenesis. The biological activity of those tumours is frequently uncertain and causes an unpredictable prognosis. The prognostic conclusion is based on a bioptic diagnosis, established by histological examination. Complete extirpation is essential.
Keywords: fibrom; Neurilemmoma; Adult; Male; nádory pleury; Fibroma; Aged; lidé; dospělí; mužské pohlaví; ženské pohlaví; senioři; lidé středního věku; neurilemom; Female; Pleural Neoplasms; Humans; Middle Aged